Menangis Menurut Tafsir Al-Maraghi Karya Ahmad Mustafa Al-Maraghi - Yuni Fitri Yasni; Inong Satriadi (IAIN Batusangkar, 2022)
The main problem in this paper is to see the many verses of the Qur'an talking about crying, making it difficult for people to distinguish where crying is recommended and crying is forbidden by the Prophet Muhammad Saw. The purpose of this study is: (1) to describe and analyze the prohibited form of crying, (2) To describe and analyze the recommended form of crying and (3) To describe and analyze the benefits of crying. The type of research that the author uses is library research with the thematic interpretation or Maudhu'i analysis method. The primary source of data in this study is Ahmad Mustafa al-Maraghi's Tafsir al-Maraghi, especially verses from the Qur'an and history related to crying. From the research that the author conducted, it can be concluded that the prohibited form of crying is pretending. Meanwhile, the recommended forms of crying are: (1) crying with emotion for the truth of the Qur'an, (2) crying, (3) crying for sincerity and, (4) crying regret for mistakes made (related to crying on the day of judgment). Then the benefits of crying are: (1) it can increase the solemnity, and (2) it is promised enjoyment by Allah Swt.